Epidemiology of pediatric road traffic injuries: a multicenter hospital-based study in Ghana - Baffour Appiah, Anthony; Lowery Wilson, Michael; Dambach, Peter; MohammadNamdar, Mahsa; Buunaaim; Alexis Dun Bo-ib; Alatiiga, John Abanga; Ativor, Vincent; Donkor, Peter; Mock, Charles (BioMed Central, 2026)
Background
Road traffic injury (RTI) is a major threat to children and adolescents worldwide. RTIs account for 25.7 deaths per 100,000 people in the general population. Unlike in other western countries where road fatalities are declining, deaths in Ghana continue to rise. This study examined the injury characteristics and spatiotemporal patterns of pediatric RTI cases and inpatient fatalities across three zones in Ghana.
Methods
This study employed a retrospective cross-sectional design, analyzing pediatric RTI data from three teaching hospitals in Ghana, with each hospital located in one of Ghana’s three geographic zones: northern, middle, and coastal/southern. The study included all pediatric RTI cases captured between 2021 and 2024. Data on sociodemographic, spatial-temporal information, type of injury, injury severity, and admission outcome were analyzed. Descriptive statistics and Chi-square tests were used to compare groups at p < 0.05. Quantum Geographic Information System (QGIS) was used to develop choropleth maps.
Results
A total of 1,485 pediatric RTI cases were included. Boys constituted 72.3%. Adolescents aged 13–18 years (45.6%) and school children aged 6–12 years (32.4%) were the most affected age groups. The leading causes of RTI were pedestrian knockdown (51.1%) and motorcycle crash (33.2%). While pedestrian knockdowns were widespread across the country, motorcycle crashes were dominant in the northern zone. Head injury was commonly reported among patients seen in the middle (60.4%) and northern (59.5%) zones, while lower limb injuries (54.3%) were most frequently seen in the southern zone. Mortality rates differed among the zones: 6.9% northern, 2.8% southern, and 0% middle (p < 0.001).
Conclusion
The differences in injury patterns, mortality rates, and crash types underscore regional disparities in risk exposure and point to the limited effectiveness of road safety interventions across the country. The local road safety authorities should intensify road safety education and law enforcement, with clear outcome indicators to monitor impacts. Improvements in road infrastructure are also necessary, which provide separate routes for pedestrians with strict adherence.